Pengaruh Kredibilitas, Kemudahan Akses, dan Review Pengguna terhadap Niat Beli di Tokopedia - Firmansyah, Dikki; Jahroni, Jahroni; Lestari, Utami Puji (Lembaga Yasin AlSys, 2025)
The rapid growth of e-commerce in Indonesia has significantly transformed consumer behavior, with Tokopedia, one of the largest platforms becoming a central focus for understanding the factors influencing purchase decisions. This study aims to examine the roles of credibility, ease of use, and user reviews in shaping purchase intention among Tokopedia customers. Using a quantitative approach and survey technique, data were collected through online questionnaires distributed to Tokopedia users via purposive sampling. Data analysis was conducted using multiple regression to test the contribution of each variable to purchase intention. The results reveal that platform credibility, ease of use, and user reviews all significantly influence consumer purchasing behavior. These three variables enhance user trust, facilitate interaction with the system, and strengthen social influence through peer reviews. The main conclusion is that these factors play a crucial role in creating a positive shopping experience and fostering purchase intention on Tokopedia. The implications highlight the importance of strategies to strengthen platform reputation, optimize user interface design, and manage reviews as part of developing a competitive e-commerce ecosystem. This study also opens opportunities for further research by considering additional variables such as digital promotion, service quality, and customer loyalty to deepen understanding of consumer behavior in the digital era.